Public Management: analysis of the status of web portals of the public entities of Ecuador and services focused on the citizen - Osejo Domínguez, Edgar Efraín (2018)
The present research develops an analysis of the state web portals with the focus towards the citizen services. Within this analysis, the following factors were reviewed: access to citizen services, quality of information available on portals, development of online services of each of the entities, capacity for interaction between users and government agencies through different mechanisms of contact and feedback by the citizen towards the public dependency. Using the bibliographical - documentary methodology, this study uses as a main reference the Multi - Dimensional model of electronic government measurement proposed by the Economic Commission for Latin America and the Caribbean (CEPAL) and several elements proposed by the National Secretariat of Public Administration (SNAP). The analysis was carried out between August 2016 and August 2017. Each government electronic portal was visited, validating its contents with the indicated factors. Once the factors validated with the contents of each electronic portal, the level of compliance of each of these was determined. From this analysis we present the results obtained by each factor.